2012
DOI: 10.2108/zsj.29.770
|View full text |Cite
|
Sign up to set email alerts
|

Scales Microstructure of Snakes from the Egyptian Area

Abstract: The morphology of many organisms seems to be related to the environments in which they live. Many snakes are so similar in their morphological patterns that it becomes quite difficult to distinguish any adaptive divergence that may have occurred. Many authors have suggested that the microstructure of the reptile's scales has important functional value. Herein, we investigate variations on the micromorphology of the external surface of dorsal scales on the head, the mid-body region (trunk), and the tail of Rhom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…It provided the corridor for the migration of the snakes from the north of Sundaland to the south in Java region (Inger and Voris 2001). The prehistoric environmental conditions also had an enormous influence on the divergence of these snakes (Allam and Abo-Eleneen 2012). However, based on the map of Heaney (1991), the Pleistocene savanna or grasslands only covered part of the area between Sumatra-Borneo and Borneo-Eastern Java.…”
Section: Relationships Among Colubridae In Sumatra and Java Islandsmentioning
confidence: 99%
“…It provided the corridor for the migration of the snakes from the north of Sundaland to the south in Java region (Inger and Voris 2001). The prehistoric environmental conditions also had an enormous influence on the divergence of these snakes (Allam and Abo-Eleneen 2012). However, based on the map of Heaney (1991), the Pleistocene savanna or grasslands only covered part of the area between Sumatra-Borneo and Borneo-Eastern Java.…”
Section: Relationships Among Colubridae In Sumatra and Java Islandsmentioning
confidence: 99%
“…Bu çalışmaların birinde dört farklı habitattan seçilen on farklı yılan türüne ait deri örneklerinin taramalı elektron miksoskobunda incelemiş ve sonuç olarak yılan derilerine ait mikro mimarilerin taksonomide kullanılabileceği rapor edilmiştir [17]. Bir başka çalışmada iki farklı yılan türüne ait deri örnekleri taramalı elektron mikroskobu ile incelenmiş ve mikroyapılarında önemli farklılık olduğunu bildirilmiştir [18]. Dört farklı yılan türünde taramalı elektron mikroskop kullanarak yapılan çalışmada incelenen deri örneklerinin mikroyapısının türler arasında önemli farklılıklar gösterdiği ve bu yöntemin taksonomide kullanılabileceği belirtilmiştir [19].…”
Section: Tartişma Ve Sonuçunclassified
“…The oberhaütchen and underlying layers may all be rucked to produce ridges on the scale surface (Harvey and Gutberlet, 1995). The overall structure of features of the oberhautchen surface and epidermal folding is referred to here as microornamentation (Ruibal, 1968, Arnold, 2002) or microstructure (Allam and Abo-Eleneen, 2012), and these features are readily studied by scanning electron microscopy. Despite this common special structure of squamate scales, Allam and Abo-Eleneen (2012) reported that the snake’s microhabitats have many impacts on the scales outer surface microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy and ultrastructure studies of the squamate scale surfaces are very important for the analysis of scale microstructures. Several studies have focused on scale microstructure and microornamentation to suggest their functional significance (Gower, 2003, Allam and Abo-Eleneen, 2012) or to simply describe microanatomy (Chiasson and Lowe, 1989, Velloso et al, 2005). In addition, microstructures and microornamentations have been used as tools in ontogenetic and/or evolutionary studies of squamates (Harvey and Gutberlet, 1995).…”
Section: Introductionmentioning
confidence: 99%